2019
DOI: 10.3892/mmr.2019.10894
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase�C promotes choline transporter‑like protein�1 function via improved cell surface expression in immortalized human hepatic cells

Abstract: choline is used to synthesize phospholipids and a lack of choline induces a number of liver-related diseases, including non-alcoholic steatohepatitis. The current study characterized the choline uptake system, at molecular and functional levels, in the immortalized human hepatic cell line, Fa2N-4, to identify the specific choline transporter involved in choline uptake. The present study also assesed whether choline deficiency or the inhibited choline uptake affected cell viability and apoptosis. reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…SAM is synthesized via choline oxidase in the inner mitochondrial membrane. Previous studies have suggested that CTL2 uptakes choline in the mitochondria, synthesizes SAM, a methyl donor, via choline oxidation, and is involved in DNA methylation [ 18 , 38 ]. Recent studies have shown that the CTL2 protein is expressed in the mitochondria isolated from platelets, and choline uptake was confirmed [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAM is synthesized via choline oxidase in the inner mitochondrial membrane. Previous studies have suggested that CTL2 uptakes choline in the mitochondria, synthesizes SAM, a methyl donor, via choline oxidation, and is involved in DNA methylation [ 18 , 38 ]. Recent studies have shown that the CTL2 protein is expressed in the mitochondria isolated from platelets, and choline uptake was confirmed [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of mRNA expression were measured according to previously established methods [ 19 , 42 , 43 ]. Total RNA was extracted from SIM-A9 cells using QIA shredder and RNeasy Mini Kit (Qiagen Inc., Valencia, CA, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The subcellular localization of CTL1 and CTL2 proteins in SIM-A9 cells was performed using immunocytochemistry with reference to previous publications [ 17 , 42 , 43 ]. SIM-A9 cells were washed with Dulbecco’s Phosphate Buffered Saline (D-PBS) (Wako), lysed in RIPA buffer (Santa Cruz Biotechnology, Inc., Dallas, TX, USA) including 1 mM ethylenediaminetetraacetic acid and a protease inhibitor cocktail on ice, and centrifuged at 14,000× g for 15 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%